Disgeusia como principal manifestación oral en pacientes con COVID-19 leve en el Instituto Nacional de Enfermedades Respiratorias - Carrasco Rueda, Carlos Alberto (2022)
Objective. To report the oral manifestations associated with COVID-19 as well as whether these persist over a period of 3 months. Methods. A longitudinal, descriptive study was carried out evaluating 149 individuals positive for SARS-CoV-2 by polymerase chain reaction (PCR), who underwent an initial examination and a control 3 months later. Results. A total of 65% of the participants reported some manifestation in the oral cavity and 24% some sequelae. Within these observed symptoms and oral sequelae, the one with the highest incidence was dysgeusia, which was found in 51% of patients followed by xerostomia (27%), lymph nodes or swollen glands (17%). These manifestations decreased significantly during the follow-up, however they prevailed in some patients. Conclusions. Dysgeusia is the oral manifestation with the highest incidence in this study and was among the 5 most common general manifestations.